Verbal retrieval deficits due to traumatic brain injury are associated with changes in event related potentials during a Go-NoGo task - Chiang, Hsueh-Sheng; Motes, Michael; Afkhami-Rohani, Borna; Adhikari, Ashna; LoBue, Christian; Kraut, Michael; Cullum, C. Munro; Hart Jr, John (Clinical neurophysiology, 2024)
•Subjects with traumatic brain injury with verbal retrieval deficits had larger N2 amplitude in NoGo than in Go trials.•Larger N2/P3 NoGo amplitude predicted faster processing speed in traumatic brain injury with verbal retrieval deficits.•Shorter P3 latency of the difference wave (NoGo – Go) predicted faster processing speed in traumatic brain injury with verbal retrieval deficits. Verbal retrieval (VR) deficits often occur after traumatic brain injury (TBI), but the mechanisms remain unclear. We examined how event-related potentials (ERPs) during a Go-NoGo task were associated with VR deficits. Sixty veterans with a history of TBI underwent a neuropsychological battery and a Go-NoGo task with concurrent EEG recording. We compared task performance and ERP measures (N2, P3) between those with and those without persistent injury-related VR deficits. We then used generalized linear modeling to examine the relationship between ERP measures and scores on measures of executive function and processing speed. Go-NoGo task performance was comparable between the groups. Those with VR deficits had larger N2 amplitude in NoGo than in Go conditions. In participants with VR deficits, larger NoGo N2/P3 amplitude predicted faster processing speed. Furthermore, larger P3 amplitude and shorter P3 latency of the difference wave (NoGo – Go) predicted faster processing speed in those with VR deficits. Despite no difference in Go-NoGo task performance, ERP amplitude and latency measures associated with cognitive control during Go-NoGo distinguished TBI individuals with VR deficits from those without. This study furthers our understanding of VR deficits in TBI and implicates potential application of ERP measures in monitoring and treating such deficits.